Экспансия-III: роман / Юлиан Семенов - Семенов Юлиан Семенович (Современник, 1989)
Экземпляры: Селтинская районная библиотека (к/х) (20220824) / Инвентарный номер: 148796 / Цена: / Авт.знак: С 30 / ГРНТИ: 17.82.31 / ББК: 84(2Pос=Рус)6